FILSAFAT MUSIK DAN POSISINYA DALAM HINDUISME - I Gede Pasek Mancapara (Sanjiwani: Jurnal Filsafat, 2022)
Music is inseparable from human life since ancient time until present, whether as self-identity, social group identity, including Hinduism, considering the role of music is very useful. Absolutely to study music from various paradigms, therefore on this opportunity examine music with the formulation of the problem; how the essence of music from a philosophical point of view and how the position of music in Hinduism. The method used in this scientific work is descriptive and interpretive qualitative. Based on the result of this study, it was found that according to the object of philosophy, music has material and formal objects. Music as a material object in the form of musical instruments and their elements, namely rhythm, melody, harmony, song form and structure also expression as a unit. The formal object of music that we can see is that music is essentially a different work of art or aesthetics, a form of culture, or according to the view of ancient Greek philosophers who viewed music, mathematics, and astronomy in relation to the universe. The position of music in Hinduism is found in the Sama Veda Samhita which teaches chanting sacred mantras / prayers of praise to God, music is bestowed by Saraswati Goddess, besides that in Hindu aesthetics it can also be found in the Gandara Veda / art sciences, Natya Sastra and Nitya Vedangga.